Parental supply of alcohol to Australian minors: an analysis of six nationally representative surveys spanning 15 years. (December 2016) - Kelly, Adrian; Chan, Gary; Weier, Megan; Quinn, Catherine; Gullo, Matthew; Connor, Jason; Hall, Wayne
Abstract Background Most adolescents begin alcohol consumption during adolescence, heavy alcohol use by adolescents is common, and alcohol-related harm amongst adolescents is a major public health burden. Parents are a common source of alcohol amongst adolescents, but little is known about how parental supply of alcohol has changed over recent years. This study examines national trends in parental supply of alcohol to adolescent children in Australia since 1998. Methods Six Australian National Drug Strategy Household Surveys (1998–2013) yielded rates of parental supply of current and first ever alcohol consumed. Lifetime and current alcohol use were also estimated. The surveys were conducted for households across all Australian states and territories. Surveyed adolescents were aged 14–17 years (N = 7357, 47.6 % male). Measures included the reported source of currently consumed alcohol and first ever alcoholic beverage (parents/friends/others), lifetime alcohol use, number of standard alcohol units consumed on drinking days, and frequency of alcohol use. Corrected Pearson chi-squared tests were used to compare survey years. Results There was a significant drop in parental supply of current alcohol use from 21.3 % in 2004 to 11.79 % in 2013 (p < .001). The lower prevalence of parental supply coincided with legislative changes on parental supply of alcohol to adolescents, but causality cannot be established because of the variation in the timing and reach of parental supply legislation, and small samples in some states. There were downward trends in adolescent experimentation, quantity and frequency of alcohol use across years, with the largest drop in alcohol use in 2010 and 2013. Conclusions In Australia, there has been a substantial reduction in parental supply of alcohol to adolescents from 2010, and this factor may partially account for reductions in adolescent alcohol use.